ANALISIS PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN VARIABEL CITRA MEREK SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN TOYOTA AVANZA NASMOCO MAJAPAHIT KOTA SEMARANG) - Permata Ambarwati, Erina; Khasanah, Imroatul (Diponegoro Journal of Management, 2018)
This research aims many people choose Toyota Agya and Calya to be purchasing decisions. It seems that with the emergence of new products like Agya and Calya this has resulted in a decrease in sales of the Toyota Avanza. to analyze factors that can affect purchase decisions by using brand image as an intervening variable. Price perception and product quality is an element that can influence it. Toyota Avanza buyer at Nasmoco Majapahit Semarang will be examined their perception about impact price perception and product quality of a product then it will affect a high purchasing decisions by consumers. This type of research use explanatory research, with a population of 100 respondents who use and buy Toyota Avanza at Nasmoco Majapahit Semarang by way of purposive sampling. Data were collected through a questionnaire with Likert scale measurement. Methods of data analysis used correlation, and multiple regression using SPSS.The result of Â this study are the perception of price and product quality affecting the brand image with a positive relationship. And brand image has a positive influence on purchasing decisions. This means that when independent factors such as price perception and product quality increasing, purchase decision Toyota Avanza atÂ  Nasmoco Majapahit Semarang also increasing significantly. This study concluded that price perception, product quality and brand image influence on purchasing decisions, either partially or simultaneously.